SPIRITUAL INTELLIGENCE LINKING TO LEADERSHIP EFFECTIVENESS: INTERCEDING ROLE OF PERSONALITY TRAITS - Sultan, Sarwat; Khan, Maria; Kanwal, Frasat (PEOPLE: International Journal of Social Sciences, 2017)
The purpose of this study was to understand the relationship between spiritual intelligence and leadership effectiveness. It was further in the objective of the current study to explore the personality traits as mediating factors between the relationship of spiritual intelligence and leadership effectiveness. Data were collected from a sample of 260 managers aged between 22 and 60 years working in different organizations in Multan. Managers provided information regarding emotional intelligence, personality traits, and leadership effectiveness. Findings revealed that spiritual intelligence was significantly related to leadership effectiveness and personality traits of extroversion and openness to experience. Result further revealed that personality trait of openness to experience was found positively correlated with leadership effectiveness. Results proposed that personality dimension of openness to experience mediated the relationship between spiritual intelligence and leadership effectiveness among managers. Implications of these findings and directions for future research are discussed.